Profile and histopathology features of top three cases of Extra Pulmonary Tuberculosis (EPTB) in West Nusa Tenggara: A retrospective cross-sectional study. (March 2022) - Djannah, Fathul; Massi, Muhammad Nasrum; Hatta, Mochammad; Bukhari, Agussalim; Hasanah, Idyatul
Abstract: Background: Tuberculosis (TB) is an infectious disease that might threaten life with a high incidence rate globally, especially in developing countries such as Indonesia. Although some TB cases are found in the lungs, the incidence of patients with extra-pulmonary TB infection also shows a significant number. However, these cases are still underreported, especially in Indonesia. Histopathological examination is one of the gold standards for diagnosing EPTB. Materials and methods: This is a cross-sectional retrospective descriptive study. This study uses data from medical records and histopathological examination results of extra-pulmonary TB patients at two hospitals in West Nusa Tenggara between May 2010 and February 2020. The inclusion criteria for this study were patients diagnosed with EPTB histopathologically and had complete paraffin block. In addition, the exclusion criteria were patients with incomplete data in the medical record. The data recorded include gender, age, organ location, area of residence, and histopathological features. Results: There were 1.817 cases of extra-pulmonary TB in West Nusa Tenggara from May 2010 to February 2020. The top three organs were from the neck (84.7%), breast (14.1%), and colon (1.2%), with a total of 1362 cases. Women dominate the top three cases of EPTB with 894 patients (65.7%) and in the age group 21–30 (28%). Central Lombok has the most EPTB patients (450; 33.07%). Microscopic examination revealed well-organized granulomas in 988 patients (72.6%) and poorly organized granulomas in 374 patients (27.4%). Conclusion: The three most frequent cases of EPTB found in West Nusa Tenggara are cervical lymphadenitis TB, mastitis TB, and colitis TB, with the majority of cases being well-organized granulomas. Further studies dealing with better designs and larger sample sizes need to be considered. The results of this study are significantly needed to determine the intervention strategies to reduce morbidity and mortality due to EPTB. Highlights: Most cases of extrapulmonary TB in Indonesia are not reported. Histopathology is one of the gold standards for the diagnosis of extrapulmonary TB. Lymphadenitis tuberculosis of the neck, mastitis tuberculosis, and intestinal tuberculosis are the most common extrapulmonary TB.